PENERAPAN KONSEP BUDGETING DALAM PENYUSUNAN RENCANA ANGGARAN PROGRAM KERJA ORKI TANGERANG SELATAN - Lina Nofiana; Hasanudin; Rizka Wahyuni Amelia (Abdi Jurnal Publikasi, 2026)
The purpose of implementing this PKM is to provide knowledge to the community, especially members of the Indonesian Fitness Sports Organization (ORKI) of South Tangerang City to know how to prepare a work budget plan by applying the concept of budgeting among ORKI members. The main objective is to provide training, direction and knowledge on how to prepare a work budget plan by applying the concept of budgeting among members of the Indonesian Fitness Organization (ORKI) of South Tangerang City to be more transparent and accountable. The method of implementing training and mentoring to members of the Indonesian Fitness Organization (ORKI) of South Tangerang City. The implementing team carried out material provision activities in the form of training in making budget plans in work programs with the training that had been carried out, making work programs in accordance with the concept of budgeting so that the work plans made were more accountable. The main objective of this work program budget plan making training was to broaden knowledge about making budget plans in work programs that could have a positive impact in the future for members of the Indonesian Fitness Organization (ORKI) of South Tangerang City.